KINERJA PERUSAHAAN DAERAH AIR MINUM TIRTA MALEM KABUPATEN KARO DALAM PELAYANAN AIR BERSIH BAGI MASYARAKAT DI KECAMATAN KABANJAHE - Purba, Rani Abigael br; Trimurni, Februati (Journal of Management Small and Medium Enterprises (SMEs), 2024)
PDAM Tirta Malem is responsible for providing clean water services to the community while contributing to advancing the local economy. However, access to clean water in Kabanjahe Regency still needs to be improved, with only 48,080 of the 75,899 residents of Kabanjahe District having access in 2018. Obstacles such as damaged pipe networks and poor financial management also affect Tirta Malem's service performance. This research aims to describe the performance of PDAM Tirta Malem by utilizing indicators of productivity, service quality, responsiveness, and accountability, as well as analyzing the factors inhibiting and driving its performance. The research method used is qualitative, collecting data through interviews, observation, documentation, and literature study. The research results show that PDAM Tirta Malem has yet to be completely successful in providing clean water services to the community in Kabanjahe District. Although there have been efforts to account for finances and prevent corruption, performance-supporting factors such as increased finances and resources and good leadership are the keys to improvement. On the other hand, inhibiting factors such as lack of human and financial resources and the problem of water theft are still challenges. Research recommendations include installing pumps at water sources, increasing supervision, improving pipe infrastructure, employee training, and implementing better business plans to improve the overall performance of PDAM Tirta Malem. Keywords: Public Service; New Public Management; Performance of Public Sector Organization